No-Touch Saphenous Vein - Vascular Damage and the London Connection - Dashwood,Michael R. (2022)
ABSTRACT In this review, I summarise the circumstances leading to the collaboration between London and Örebro on the basic research performed to study potential mechanisms underlying the improved patency of saphenous veins harvested by the no-touch technique. Histological studies reveal various forms of vascular damage to saphenous vein grafts harvested in conventional coronary artery bypass grafting (CABG) whereas no-touch grafts retain a normal architecture. The perivascular fat that remains intact on no-touch saphenous vein grafts seems to play a particularly important role as the “protector” of all layers of the graft. In addition, the perivascular fat is a source of adipose cell-derived factors that may contribute to the success of the no-touch technique. While a number of trials have compared no-touch with conventional grafts following CABG, these have generally been limited to short follow-up periods, low patient numbers, and inadequate histological data. When handling no-touch saphenous vein at harvesting, there is no direct contact of the vein by surgical instruments, spasm does not occur, and high-pressure intraluminal distension is not required. While damage to both endothelial and vascular smooth muscle cells are evident at the microscopic and ultrastructural level in conventional saphenous vein grafts, their structure in no-touch grafts is preserved. Also, in no-touch veins, the vasa vasorum remains intact and transmural blood supply is maintained. This microvascular network is disrupted during conventional harvesting, a situation likely to stimulate processes involved in graft occlusion. The use of excess graft material for histology is to be encouraged for the assessment of vascular damage and even surgeon competence. If you don’t look, you don’t find.